1997
DOI: 10.1177/088532829701100403
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Polyethylene Glycol Graftings on the in Vitro Degradation and Calcification of Bovine Pericardium

Abstract: Calcification is a frequent cause of the clinical failure of bio-prosthetic heart valves fabricated from glutaraldehyde pretreated bovine pericardium (GATBP). This article reports on various chemical techniques for grafting polyethylene glycol (PEG) on bovine pericardium, their biostability, and calcification. The process of calcification profile was studied by in vitro experiments via the incubation of pericardial samples in a metastable solution of calcium phosphate. The calcification profile of PEG-modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2025
2025

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…For that, 450 mg of hirudin-encapsulated alginate beads were exposed overnight to 2.5% glutaraldehyde vapors. They were further incubated in 5% solution of polyethylene glycol (PEG-20,000) in 0.1 M Tris-HCl buffer, pH 5.0 for 5 h. 26 The PEGgrafted samples were then washed with distilled water to remove the unattached PEGs, then were air dried.…”
Section: Microcapsule Formationmentioning
confidence: 99%
“…For that, 450 mg of hirudin-encapsulated alginate beads were exposed overnight to 2.5% glutaraldehyde vapors. They were further incubated in 5% solution of polyethylene glycol (PEG-20,000) in 0.1 M Tris-HCl buffer, pH 5.0 for 5 h. 26 The PEGgrafted samples were then washed with distilled water to remove the unattached PEGs, then were air dried.…”
Section: Microcapsule Formationmentioning
confidence: 99%
“…Nagaoka et al33 synthesized a graft copolymer of methacrylates with PEG and found the resulting polymer to be quite nonthrombogenic. Recent studies of Vasudev et al34–36 have demonstrated that the surface grafting of bovine pericardium through high molecular weight PEG via glutaraldehyde linkages can provide new ways of controlling tissue biodegradation, calcification, and thrombosis. Thus, these new microcapsules fabricated from PLA–PEG may serve to provide controlled taxol delivery and immunoprotection, whereas the outer layer of PEG may serve to enhance biocompatibility and reduce biodegradation.…”
Section: Discussionmentioning
confidence: 99%
“…The calcium (CaCl 2 2H 2 O) and phosphate (K 2 H PO 4 ) solutions were prepared in 0.1 M Tris buffer (pH 7.4) containing 0.03% methyl 4‐hydroxy benzoate and 0.01% propyl 4‐hydroxy benzoate as preservatives. Equal volumes of doubled concentrations of 2.57 m M calcium and 1.54 m M phosphate were mixed in a screw cap bottle containing the pericardial tissues ( 11, 18). These solutions were also incorporated with a protein mixture containing 25 mg% albumin, 15 mg%γ‐globulin, and 7.5 mg% fibrinogen.…”
Section: Methodsmentioning
confidence: 99%
“…Two major approaches to reduce the calcification of tissue prostheses have been attempted. First, implant modification has been attempted to prevent calcification by precoating surfaces with various agents such as diphosphonates, sodium dodecyl sulphate, protamine sulphate, aluminum and ferric ions, or 2‐amino oleic acid ( 9, 10) or grafting polyethylene glycols ( 11, 12). Second, local polymeric delivery of some of these agents ( 13, 14) has been attempted.…”
mentioning
confidence: 99%